Perbaikan Fraksi Lipid Serum Tikus Putih Hiperkolesterolemi Setelah Pemberian Jus dari Berbagai Olahan Tomat (Hypercholesterolemia Albino Rat Lipid Fraction Improvement After Giving Tomato Juice) - Retno Sri Iswari (Biosaintifika: Journal of Biology & Biology Education, 2009)
This research would like to show the effect of tomato juice in a variety processing method towards hypercholesterolemia albino rat blood plasma lipid fraction. The special purpose if to know and analyze tomato juice advantages towards total cholesterol content, LDL–cholesterol, HDL–cholesterol and triglyceride. The research design is a Post Test Randomized Control Design by means of Complete Randomized Design (RAL). There are 4 groups of treatment, each groups has 6 repeaters. The data is tested by One Way Varian Analyze. If there is a significance difference, there will be Duncan’s New Multiple Range Test followed. The research shows that there is a significance difference of total cholesterol content, LDL–cholesterol, HDL–cholesterol and triglyceride. The highest total cholesterol content, LDL–cholesterol and blood plasma triglyceride content are on the hypercholesterolemia control group. The lowest total cholesterol content, LDL–cholesterol and blood plasma triglyceride content are on the group that is given by a fried tomato juice. The lowest HDL content is on the hypercholesterolemia control group and the highest one are on the group that is given by a fried tomato juice. The research conclusion is that tomato juice supplementation able to fix hypercholesterolemia albino rat blood plasma lipid fraction, especially to decrease total cholesterol content, LDL–cholesterol and blood plasma triglyceride, and increase hypercholesterolemia albino rat blood plasma HDL-cholesterol content. Fried tomato juice give the best effect on decreasing total cholesterol content, LDL–cholesterol and triglyceride and increasing blood plasma HDL-cholesterol content. Keywords: hypercholesterolemia albino rat, total cholesterol content, LDL–cholesterol, HDL–cholesterol, triglyceride